OPTIMIZING MATHEMATICS LEARNING OUTCOMES USING ARTIFICIAL INTELLIGENCE TECHNOLOGY: OPTIMALISASI HASIL PEMBELAJARAN MATEMATIKA MENGGUNAKAN TEKNOLOGI ARTIFICIAL INTELLIGENCE - Tulak, Topanus; Rubianus; Maramba', Sarah (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2024)
The use of technology in learning has become inevitable in modern education. It plays an important role in optimizing the learning process, including in the context of mathematics learning. This study aims to describe the optimization of mathematics learning outcomes using Artificial Intelligence technology. This research uses a qualitative method with a descriptive approach. The instruments used were tests and interviews. The data collected was then analyzed using the interactive model analysis flow developed by Miles and Huberman, namely reducing data, presenting data, and verifying/concluding. The results showed that by using Artificial Intelligence (AI) technology in the learning process, lecturers can provide experiences tailored to students' individual needs, improve their understanding of mathematical concepts, and provide fast and precise feedback. Thus, the use of AI technology can optimize mathematics learning.